Rancang Bangun Wireless Router Menggunakan Raspberry PI - Adhiwibowo, Whisnumurti; Ardiansyah, Baik Catur (Universitas Semarang, 2018)
Raspberry Pi is a credit card-sized SBC (Single Board Computer) developed by the Raspberry Pi Foundation in the UK with the aim of teaching basic computer science at school. Raspberry Pi can be used for various things including wireless. In this study will be carried out the implementation of wireless routers by using Raspberry Pi as the main media. This is done to implement the use of Raspberry Pi devices as an alternative to Wireless Routers or in the world of networking. The Wireless Router implementation method used is the PPDIOO network cycle method owned by CISCO which has the stages of Prepare, Plan, Design, Implement, Operate, and Optimize. Wireless Router implementation uses several devices between Edimax - Wireless 802.11b / g / n usb wireless adapter as a device or Broadcast Wireless Raspberry Pi media as the main function of the device and system owned by the Wireless Router. Wireless Routers using Raspberry Pi become one of the best solutions for the needs of adding new wireless network segments if you see in terms of limited funds and existing devices. An administrator will easily build a new network using Raspberry Pi.